Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1741-2552/ab3c95
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methodologies for computing the deep brain stimulation volume of tissue activated

Abstract: Objective. Computational models are a popular tool for predicting the effects of deep brain stimulation (DBS) on neural tissue. One commonly used model, the volume of tissue activated (VTA), is computed using multiple methodologies. We quantified differences in the VTAs generated by five methodologies: the traditional axon model method, the electric field norm, and three activating function based approaches—the activating function at each grid point in the tangential direction (AF-Tan) or in the maximally acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 48 publications
2
76
0
1
Order By: Relevance
“…In this work, we focused exclusively on monopolar stimulation modeled with the axon model method. We have previously shown that all standard VTA methods for monopolar stimulation yield similar results 18 — however, these similarities break down with bipolar stimulation. Thus, if one were to choose to expand our work to bipolar stimulation, it may also be necessary to test several methods of VTA computation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this work, we focused exclusively on monopolar stimulation modeled with the axon model method. We have previously shown that all standard VTA methods for monopolar stimulation yield similar results 18 — however, these similarities break down with bipolar stimulation. Thus, if one were to choose to expand our work to bipolar stimulation, it may also be necessary to test several methods of VTA computation.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, we repeated experiments with different conductivities, including and excluding an encapsulation layer and found that while activation thresholds changed in response to changes in conductivity layer, the conclusions were similar regardless of conditions. We implemented a Dirichlet boundary condition at the outer edge of the model to serve as a distant ground 1,8,18 (100 mm x 100 mm x 100 mm) and solved for the electric potential solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct bounding VTA method used here therefore resulted in VTAs that were larger at the anode than previously reported. There was evidence that previously reported method likely underestimated the activations near the anode (Slopsema et al, 2018;Anderson et al, 2019;Duffley et al, 2019), therefore, the method used here that incorporates multiple orientations orthogonal to the lead offered a more directly interpretable VTA activation profile, especially for a larger target such as the globus pallidus, and especially with a lead with larger vertical spacing (1.5 mm). However, a bigger VTA produced by bipolar stimulations does not directly translate to better therapy or equate with lower side effect threshold-the shape of the VTA matters more in terms of overlapping with therapy regions and side effect pathway activations.…”
Section: Limitations Of Bipolar Vtamentioning
confidence: 87%
“…Lead-DBS uses a VTA model that thresholds the E-Field magnitude as this practice was suggested to yield good approximations by others (Åström et al, 2015). However, recent results by leading groups in this field suggested significant limitations of the approach (Duffley et al, 2019;Gunalan et al, 2017). Moreover, limitations apply to the concept of the VTA itself.…”
Section: Limitationsmentioning
confidence: 99%